Pedagogical Choices in Teaching Social Studies in Lower Primary Classrooms in Nigeria - Martin Chukwudi Ekeh; Sarita Ramsaroop (Indonesian Journal of Early Childhood Education Studies, 2023)
This research reports teachers’ pedagogical choices in teaching social studies in lower primary classrooms in Nigeria. It is believed that neglecting the prescribed curriculum and teachers’ pedagogical choices impacts social studies objectives. The research intended to (a) explore the pedagogical approaches prescribed in the social studies curriculum for primaries one and two, (b) to understand teachers’ pedagogical preferences in teaching primary one and two learners’ social studies, and (c) to examine teachers’ application of free play and mutually directed play pedagogies in teaching primary one and two social studies. The study was conducted in Okigwe Education Zone, Imo State, Nigeria, using a qualitative research approach and a generic qualitative research design. The study participants were made up of primary one and two teachers of social studies (three primary one teachers and three primary two teachers) and primary one and two social studies curriculum documents. The participants were purposively sampled with the criteria that the teachers and social studies curriculum documents must be for the primary one and two learners in the Okigwe Education zone of Imo State. Data collection involved semi-structured interviews and documents, which were analysed using document and thematic data analysis. Findings indicate that whereas teachers were conversant in using teacher-led pedagogies, facilitating learning using free play was lacking. It was also discovered that teachers scarcely used resource persons, field trips, illustrations and experiential learning approaches in facilitating social studies. In conclusion, professional development training for teachers to adequately incorporate free play or learner-led pedagogies was recommended.